2010
DOI: 10.3727/096368910x494885
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stromal Cells and their Derivative, SB623 Cells, Rescue Neural Cells via Trophic Support following in Vitro Ischemia

Abstract: Cell transplantation is a promising treatment strategy for many neurological disorders, including stroke, which can target multiple therapeutic mechanisms in a sustained fashion. We investigated the ability of human mesenchymal stromal cells (MSCs) and MSC-derived SB623 cells to rescue neural cells via trophic support following an in vitro stroke model. Following oxygen glucose deprivation, cortical neurons or hippocampal slices were cocultured with either MSCs or SB623 cells separated by a semiporous membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 47 publications
1
71
1
Order By: Relevance
“…After transplantation of extracellular vesicles, the quantity of B cells, NK cells, and T cells was all increased. Recent studies have confirmed that MSC transplantation can restrain inflammatory reactions involving the brain [21,22]. In the current study, we did not find that changes in cerebral stroke could induce infiltration of immune cells after extracellular vesicle transplantation, which is in contrast to previous reports.…”
Section: Discussioncontrasting
confidence: 56%
“…After transplantation of extracellular vesicles, the quantity of B cells, NK cells, and T cells was all increased. Recent studies have confirmed that MSC transplantation can restrain inflammatory reactions involving the brain [21,22]. In the current study, we did not find that changes in cerebral stroke could induce infiltration of immune cells after extracellular vesicle transplantation, which is in contrast to previous reports.…”
Section: Discussioncontrasting
confidence: 56%
“…One of the possibilities is a mechanism involving the effects of neurotrophic growth factors and/or cytokines generated by the endogenous neural stem cells and the MSC in the huADSC. The infused huADSC may be involved in eliciting repair of tissue damage or regeneration of lost nerve cells to facilitate motional improvement of the ICH induced rats, as speculated by other investigators previously [14,33,34]. Alternatively, the huADSC may participate in angiogenesis or neoangiogenesis, providing better circulation to regenerate lost brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We and other studies demonstrated MSCs treatment increased VEGF expression and angiogenesis in ischemic rats brain [158,159]. In addition, in vitro studies showed that VEGF increased in the conditioned medium of MSCs [160]. Further studies showed that angiogenic gene-modified stem cells had better angiogenic and therapeutic effects for stroke [13,[161][162][163].…”
Section: Mechanism Of Stem Cell Therapy In Strokementioning
confidence: 91%